Metabolites from Actinomyces strain H6552 extract inhibit transforming growth factor mediated pulmonary fibrosis - Koh, Rhun Yian; Lim, Chooi Ling; Ho, Coy Choke; Uhal, Bruce David; Abdullah, Maha; Vidyadaran, Sharmili; Seow, Heng Fong (Pharmacotherapy Group, Faculty of Pharmacy, University of Benin, 2014)
Purpose: To evaluate the effects of H6552 extract in inhibiting transforming growth factor (TGF)-mediated pulmonary fibrosis in vitro and in vivo. Methods: Maximum-nontoxic dose (MNTD) of Actinomyces H6552 extract was determined using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphhenyltetrazolium bromide (MTT) assay. Effect of the extract on IMR-90 lung fibroblasts proliferation was determined by calculating the population doubling time (PDT). Collagen gel contraction assay was carried out to determine cell contractility while α-smooth muscle actin (SMA) level in cells was evaluated by quantitative real-time polymerase chain reaction (PCR) and immunostaining methods. A bleomycin-induced ICR mouse model was used in the study to determine the effect of the extract in vivo. The animals received treatments in two regimes: early treatment in which treatment was given on Day 0 and delayed treatment with treatment on Days 5 and 10. The animals were sacrificed on Day 14 and the lungs removed for histopathological assessment. Results: The MNTD of the H6552 extract was 1625 ± 459.62 μg/ml. H6552 extract significantly reduced TGF- β-mediated cell proliferation, gel contraction and α-SMA expression. PDT was increased up to 83.84 % in the treated cells. Gel contraction was inhibited by the addition of 1000 μg/ml of H6552 extract. Immunostaining results revealed negligible α-SMA antibody staining after H6552 extract treatment at 500 μg/ml. The extract also inhibited lung injury (54 % reduction in Ashcroft score) when early treatment was provided. Delayed treatment with the extract did not show any significant changes in the animals. Conclusion: H6552 extract inhibited TGF-β-induced pulmonary fibrosis and elucidation of its bioactive metabolites may yield a potential agent to treat the disease.